Utilization of Colonial Heritage Learning Resources in Locality-Based Senior High School - Ulul Fikriyani; Totok Hari Prasetiyo; Mahfud, Mahfud (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
District Tegaldlimo is a district that is located in South Banyuwangi which are named Alas Purwo National Park in Java language which is defined as "the beginning of the forest", there are some historical relics Dutch and Japanese colonial period in this district. This study focuses on the problems: (1) the potential of heritage Dutch colonial era in District Tegaldlimo, (2) the potential of heritage Dutch colonial era in District Tegaldlimo, and (3) Utilization of heritage Dutch colonial era and Japan as a source of learning the history of high school students , The results of this research are: Historical evidence in the Dutch colonial era in District Tegaldlimo either: (1) Dam Limo, (2) Railway Lori, and (3) Monument Military Aggression I or commonly called the Monument Koptu Ruswadi, then the Japanese colonial era historical relics in District Tegaldlimo, either: (1) Battery Japan, (2) Tubs, (3) Bunker Japan, and (4) Caves Japan. Thus the Dutch and Japanese heritage can be used as a source of learning history in high school students in the Basic Competence 3.5 is "Analyzing the nature of the occupation and the response of the Indonesian nation". and Basic Competence 3:10 namely "Analyzing strategies and forms of struggle of Indonesia in an effort to maintain its independence from the threat of the Allies and the Netherlands". 5 is "Analyzing the nature of the occupation and the response of the Indonesian nation". and Basic Competence 3:10 namely "Analyzing strategies and forms of struggle of Indonesia in an effort to maintain its independence from the threat of the Allies and the Netherlands". 5 is "Analyzing the nature of the occupation and the response of the Indonesian nation". and Basic Competence 3:10 namely "Analyzing strategies and forms of struggle of Indonesia in an effort to maintain its independence from the threat of the Allies and the Netherlands".